Pembentukan Perilaku Keagamaan Siswa oleh Guru Agama - Djunaidi; Kristiani (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2022)
Religious behavior can affect the conscience of students in worship and morality. The purpose of this study is to describe the behavior and character of students in worship, to describe the stages of Islamic religious education teachers in changing students' worship behavior and behavior. This research uses descriptive qualitative method. The method used is an educational method, through a psychological approach and a social approach. The data was processed using descriptive analysis techniques. The conclusion of this study shows that the religious behavior and personality of students are not in accordance with the religious behavior taught in Islam. Islamic Religion teachers try to shape religious behavior, map changes in student behavior in relation to their emotions, describe their worship behavior and personality, evaluate students' worship behavior and activities as a form of preserving their religious behavior, develop religious behavior through Islam, religious education lessons provide positive punishments that have a deterrent effect .